Arhetipske podobe vzhodnjaštva - Tomažinčič, Špela (Keria (Ljubljana), 2009)
The Carthage passage in Books 1-4 of the Aeneid serves as a literary starting-point for discussing the formation and the dynamics of Aeneasć ethnicidentity, as well as the related ethnic identity of the Romans in general. The interpretation of the passage draws on the term ćThe Otherć and the derogatory stereotype of the universal other invented during the Persian wars. The article argues that the Carthage passage forms the image of a historical and literary Other by pairing the mythical other, the Trojans, withthe historical Carthaginians. The Vergilian archetypal images of Oriental otherness are perceived as a speculum morum, which reflects the problematic Roman ethnic heritage of Troy, calling for an ethnic change.
Keywords: etnična identiteta; latinska književnost; literarne študije; rasizem; Rimljani; rimska književnost